PELAKSANAAN UU NOMOR 6 TAHUN 2014 TERKAIT DENGAN KEWENANGAN KEPALA DESA DALAM PELAKSANAAN OTONOMI DESA DI DESA JATISOBO KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Giovera, Nurulita Anggi; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2023)
This study aims to analyze and examine the authority of the head in the implementation of village autonomy as well as supporting and hindering factors in its implementation, especially in Jatisobo Village according to Law Number 6 of 2014. This research is an empirical legal research by taking empirical facts obtained from interviews and village supervision. live. Empirical research is also used to store the results of human behavior in the form of physical inheritance and, the types and sources of data used are primary data and secondary data. The nature of the research used is descriptive qualitative research using the constitutional approach, the case approach, the historical approach, and the conceptual approach. The technical analysis of legal materials used in this research is deduction using the syllogistic method, namely the analysis of legal materials prioritizes logical thinking so as to find the causes and effects that will occur. The results show that the implementation of village autonomy in Jatisobo Village has been very good, it can be seen from the implementation of the Jatisobo Village government which is already oriented towards community development and empowerment, which has been supported by good supporting factors in terms of human resources and community participation in achieving village development that is independently.